2018
DOI: 10.2147/cmar.s187973
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA 1308 promotes cell invasion by regulating the miR-124/ADAM 15 axis in non-small-cell lung cancer cells

Abstract: PurposeEmerging evidence suggests that many differentially expressed long non-coding RNAs (lncRNAs) are involved in tumorigenesis. However, the functional roles of these transcripts and the mechanisms responsible for their deregulation in non-small-cell lung cancer (NSCLC) remain elusive. Here, we identified a novel lncRNA (lncRNA 1308), which was significantly upregulated in NSCLC tissues and investigated its biological function and potential molecular mechanism.MethodsDifferences in the lncRNA expression pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 35 publications
0
21
0
Order By: Relevance
“…Downregulation of plasma miR-124 expression was a predictive biomarker for prognosis of glioma [10,22]. A large number of previous studies have suggested that miR-124 could be used as a molecular marker for tumor progression in cervical cancer [23,24], breast cancer [12,25,26], lung cancer [27,28], and osteosarcoma [29]. Numerous clinical studies have shown that BRCA is the most common type of breast cancer and has poor prognosis survival, and the pathogenesis of breast cancer involves a variety of factors and genes [4,30].…”
Section: Discussionmentioning
confidence: 99%
“…Downregulation of plasma miR-124 expression was a predictive biomarker for prognosis of glioma [10,22]. A large number of previous studies have suggested that miR-124 could be used as a molecular marker for tumor progression in cervical cancer [23,24], breast cancer [12,25,26], lung cancer [27,28], and osteosarcoma [29]. Numerous clinical studies have shown that BRCA is the most common type of breast cancer and has poor prognosis survival, and the pathogenesis of breast cancer involves a variety of factors and genes [4,30].…”
Section: Discussionmentioning
confidence: 99%
“…miR‐124 can bind to the 3'‐UTR of CDH2 to inhibit nonsmall cell lung cancer (NSCLC) cell proliferation invasion . Li et al suggested that lncRNA 1308 may function as a competing endogenous RNA (ceRNA) for miR‐124 to regulate lung cancer cell invasion through the miR‐124/ADAM 15 (a disintegrin and a metalloproteinase 15) signaling pathway, indicating that lncRNA 1308 and miR‐124 both have important roles in the disease progression of NSCLC . Tang et al also demonstrated that long noncoding RNA (OGFRP1) could sponge miR‐124‐3p and work as a ceRNA to increase the miR‐124 downstream target gene LYPD3, implying that OGFRP1 and miR‐124‐3p could be novel therapeutic targets for lung cancer .…”
Section: Mir‐124 and Other Malignant Tumorsmentioning
confidence: 99%
“…104 Li et al suggested that lncRNA 1308 may function as a competing endogenous RNA (ceRNA) for miR-124 to regulate lung cancer cell invasion through the miR-124/ADAM 15 (a disintegrin and a metalloproteinase 15) signaling pathway, indicating that lncRNA 1308 and miR-124 both have important roles in the disease progression of NSCLC. 105 Tang et al also demonstrated that long noncoding RNA (OGFRP1) could sponge miR-124-3p and work as a ceRNA to increase the miR-124 downstream target gene LYPD3, implying that OGFRP1 and miR-124-3p could be novel therapeutic targets for lung cancer. 106 Xiao et al found that miR-124 was significantly decreased in nasopharyngeal carcinoma (NPC) and that a miR-124 mimic could inhibit NPC cell (CNE1 and CNE2) proliferation, migration, and invasion via binding with the target gene forkhead box Q1 (Foxq1).…”
Section: Malignant Tumorsmentioning
confidence: 99%
“…tRF/miR-1308 was considerably overexpression in non-small-cell lung cancer tissues (NSCLC). Concurrent tRF/miR-1308 and miR-124 are effects on ADAM15 gene expression and up-regulated it (35). ADAM 15 is involved in the invasion and progression of tumors by up-regulating the matrix metallopeptidase 9 (MM9) expression in NSCLC patients, MM9 is a key regulator of cell invasion and promote lung cancer cell metastasis (36,37).…”
Section: Discussionmentioning
confidence: 99%